Peningkatan Pertumbuhan dan Produksi Tanaman Bayam Merah Organik (Amaranthus Dubius) Melalui Pemberian Macam Pupuk Organik Cair (POC) - Shelvy Fahmi Widayati; Choirul Anam; Dian Eka Kusumawati (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Indonesians often consume spinach, a commodity vegetable crop. Red spinach, or Amaranthus dubius, is one of the spinach varieties. Red spinach is a protein-rich food, especially in underdeveloped countries. Red spinach often contains higher amounts of vitamin C as well as flavonoid and anthocyanin chemicals than green spinach. The consumption value of spinach, including red spinach, has skyrocketed due to its high nutritional content. Using appropriate planting methods, such as fertilization techniques, is one strategy to boost output. The addition of liquid organic fertilizer (POC) is one of the nutrients. The objective of this study was to ascertain how different types of liquid organic fertilizers affect the development and yield of red spinach plants. One component, the type of liquid organic fertilizer, with seven levels, was put into a randomized group design. Fisher's variance (F test at 5% level) was used to analyze the observation data. The Least Significant Difference Test (BNT 5%) was conducted if there was a significant difference. When comparing the effects of several types of liquid organic fertilizers on the development and yield of red spinach plants, POC Biotani Plus treatment produced the greatest results.